Identifying soil N2O sources by combining laboratory experiments with process-based models - Yan, Zhifeng; Chu, Zhaopei; Grosz, Balázs; Chang, Baoxuan; Shurpali, Narasinha; Liu, Gang; Li, Zhaolei; Zheng, Jinsen; Li, Si-liang; Butterbach-Bahl, Klaus (Springer Nature, 2025)
Nitrification and denitrification are two important biological processes producing N2O in soils, but their contributions to N2O emissions are not well understood, hindering precise mitigationmeasures. Here, we developed process-based models (PBM) with and without transport (T) to partition N2O sources by tracking nitrogen flows (NF) through different reaction pathways. The model with transport (PBM-T-NF) well predicted N2O production from nitrification and denitrification in two different repacked soils with a shallow depth of 8 mm under moisture conditions ranging from 40 to 100% waterfilled pore space (WFPS), demonstrating its robustness and reliability. In comparison, the model without transport (PBM-NF) failed to capture the N2O dynamics and the relative contribution of denitrification to N2O production (CD), highlighting the need of including mass transport in predicting N2O dynamics. The PBM-T-NF model was further employed to investigate the effects of soil properties on N2O emissions and sources. Increased NH4+ concentration significantly decreased CD under relatively low moisture conditions, while increased NO3− slightly promoted CD over different moisture contents, emphasizing the importance of substrate availability and moisture conditions in controlling CD. Furthermore, the PBMT-NF model was used to quantify N2O sources from n artificial soil core of 80 mm depth. Soil depth was shown to be important in mediating CD by controlling O2 diffusivity, which is highly dependent on moisture content. Given the long-standing challenge in experimental quantification of N2O sources from soils, our developed model provides a novel way to estimate N2O production from different nitrogen processes, which is key for accurately targeting mitigation of N2O emissions from soils.
Keywords: nitrification; denitrification; nitrous oxide; process-based model; mass transport